Who was Ben Franklin? /Biography-Easy reader - Fradin, Dennis B.; O'Brien, John, 1953- (New York : Grosset & Dunlap, 2002)
A biography of the eighteenth-century printer, publisher, inventor, scientist, and statesman who played an influential role in the early history of the United States.
Keywords: Franklin, Benjamin, -- 1706-1790 -- Juvenile literature; Franklin, Benjamin, -- 1706-1790.; Statesmen -- United States -- Biography -- Juvenile literature; Scientists -- United States -- Biography -- Juvenile literature; Inventors -- United States -- Biography -- Juvenile literature; Printers -- United States -- Biography -- Juvenile literature; Statesmen; Scientists; Inventors; Printers